Iron profiles of preterm infants at two months of chronological age - Henny Adriani Puspitasari; Endang Windiastuti; Aryono Hendarto (Paediatrica Indonesiana, 2016)
Background Preterm infants are vulnerable to iron deficiency (ID) due to lack of maternal iron stores, repeated phlebotomy, and the body’s increased demand for iron during growth. The risk of ID increases at 2 months of age, when hemoglobin (Hb) levels start to decrease. Adequacy of body iron level is assessed by ferritin, serum iron (SI), transferrin saturation (Tfsat), total iron-binding capacity (TIBC), and Hb measurements. Objective To describe iron profiles in preterm infants at 2 months of chronological age (CA). Methods This cross-sectional study was conducted in 2-month-old infants, born at 32-36 weeks of gestational age, and who visited the Growth and Development Clinics at Cipto Mangunkusumo, Fatmawati, or Budi Kemuliaan Hospitals. Parental interviews and medical record reviews were done during the clinic visits. Complete blood count, blood smear, SI, TIBC, Tfsat, and ferritin level tests were performed. Results Eighty-three subjects were enrolled in this study. Most subjects were male (51%) and born to mothers >20 years of age (93%). Subjects’ birth weights ranged from 1,180 g to 2,550 g. The prevalence of iron deficiency anemia (IDA) was 6% and that of ID was 10%. The lowest Hb level found in IDA infants was 6.8 g/dL, while the lowest ferritin level was 8.6 ng/mL. Median values for the other tests were as follows: SI 48 µg/dL, TIBC 329µg/dL, and Tfsat 17%. Subjects with IDA were all male (5/5), mostly achieved more than twice their birth weight (4/5), were non-iron supplemented (3/5), born to mothers with low educational background (3/5), and of low socioeconomic status (3/5). Conclusion The prevalence of IDA is 6% and that of ID is 10%. Most subjects with ID and IDA have low SI, high TIBC, low Tfsat, and low ferritin level. Most of the all-male IDA subjects weigh more than twice their birth weight, are non-iron supplemented, and born to mothers with low educational background and low socioeconomic status.